Determinasi Kesejahteraan Keluarga Petani Tambak Pembenihan Ikan Bandeng di Desa Banyupoh - Salsabila Jawza Puteri; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
The low income of milkfish seed pond farmers reflects a level of welfare that is not yet optimal in improving the quality of life and family economy. This research aims to analyze the influence of competence, adoption of information technology, and land area on the welfare of families of milkfish hatchery pond farmers in Banyupoh Village. The research method used was quantitative with a simple random sampling technique involving 75 pond farmers. Data analysis used multiple linear regression analysis. The research results show that partially, competency, adoption of information technology, and land area have a significant effect on the welfare of farming families. Meanwhile, land area does not have a significant influence. However, simultaneously competence, adoption of information technology, and land area influence the welfare of farming families. Future researchers are advised to consider other factors outside research such as capital, social support, institutions, government policies and socio-economics.